2020
DOI: 10.2174/1574888x15666200408113630
|View full text |Cite
|
Sign up to set email alerts
|

Bio-mimicking Shear Stress Environments for Enhancing Mesenchymal Stem Cell Differentiation

Abstract: : Mesenchymal stem cells (MSCs) are multipotent stromal cells, with the ability to differentiate into mesodermal (e.g. adipocyte, chondrocyte, hematopoietic, myocyte, osteoblast), ectodermal (e.g. epithelial, neural) and endodermal (e.g. hepatocyte, islet cell) lineages based on the type of induction cues provided. As compared to embryonic stem cells, MSCs hold multitude of advantages from a clinical translation perspective, including ease of isolation, low immunogenicity and limited ethical concerns. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…In periodontal tissue, PDL cells are exposed to interstitial fluid shear stress during tooth movement [43,44]. Shear stress has been shown to play an essential role in cell behaviour in several cell types including embryonic stem cells [45], osteocytes [46], endothelial cells [47], MSCs [48] as well as PDL cells [43,[49][50][51][52][53]. Previously, in vitro shear stress stimulation (3-15 dyn/cm 2 ) was shown to modulate PDL cell properties such as osteogenic differentiation, cell proliferation and ECM remodelling [49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…In periodontal tissue, PDL cells are exposed to interstitial fluid shear stress during tooth movement [43,44]. Shear stress has been shown to play an essential role in cell behaviour in several cell types including embryonic stem cells [45], osteocytes [46], endothelial cells [47], MSCs [48] as well as PDL cells [43,[49][50][51][52][53]. Previously, in vitro shear stress stimulation (3-15 dyn/cm 2 ) was shown to modulate PDL cell properties such as osteogenic differentiation, cell proliferation and ECM remodelling [49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Models simplifying the bone scaffold to porous media as well as based on microCT scans have been reported using a broad range of perfusion velocity, porosity, and permeability. Shear stress caused by fluid perfusion is in fact widely recognized in the literature as a trigger of hMSC pro-osteogenic commitment (reviewed in [ 61 ]). Particularly, Melke et al [ 62 ] concluded that a wall shear stress of 0.5–10 mPa promotes mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation and expansion of cells is an important indicator that re ects the number of cells, and the extracellular matrix is closely related to the functional state of cells, and is an important indicator of cell quality [5,6]. It is signi cant that proliferation under the premise of maintaining good cell biological performance [7,8]. In terms of promoting the proliferation of stem cells, research on cell co-culture [9], cytokines [10], cellular pathways [11], gene modi cation [12,13] and other aspects have achieved relatively rich research results.…”
Section: Discussionmentioning
confidence: 99%